Potentiation of neurotoxicity in double-mutant mice with Pink1 ablation and A53T-SNCA overexpression - Suzana Gispert; Nadine Brehm; Jonas Weil; Kay Seidel; Udo Rüb; Beatrice Kern; Michael Walter; Jochen Roeper; Georg Auburger (2014)
The common age-related neurodegeneration of Parkinson's disease can result from dominant causes like increased dosage of vesicle-associated alpha-synuclein (SNCA) or recessive causes like deficiency of mitophagy factor PINK1. Interactions between these triggers and their convergence onto shared pathways are crucial, but currently conflicting evidence exists. Here, we crossed previously characterized mice with A53T-SNCA overexpression and with Pink1 deletion to generate double mutants (DMs). We studied their lifespan and behavior, histological and molecular anomalies at late and early ages. DM animals showed potentiated phenotypes in comparison with both single mutants (SMs), with reduced survival and strongly reduced spontaneous movements from the age of 3 months onwards. In contrast to SMs, a quarter of DM animals manifested progressive paralysis at ages >1 year and exhibited protein aggregates immunopositive for pSer129-SNCA, p62 and ubiquitin in spinal cord and basal brain. Brain proteome quantifications of ubiquitination sites documented altered degradation of SNCA and the DNA-damage marker H2AX at the age of 18 months. Global brain transcriptome profiles and qPCR validation experiments identified many consistent transcriptional dysregulations already at the age of 6 weeks, which were absent from SMs. The observed downregulations for Dapk1, Dcaf17, Rab42 and the novel SNCA-marker Lect1 as well as the upregulations for Dctn5, Mrpl9, Tmem181a, Xaf1 and H2afx reflect changes in ubiquitination, mitochondrial/synaptic/microtubular/cell adhesion dynamics and DNA damage. Thus, our study confirmed that SNCA-triggered neurotoxicity is exacerbated by the absence of PINK1 and identified a novel molecular signature that is detectable early in the course of this double pathology.